Model Kurva Sintering: Tinjauan Kurva Densifikasi - I Nyoman Sudiana; Muhammad Zamrun Firihu (Jurnal Aplikasi Fisika, 2016)
The study about sintering stages on alumina ceramics based on densification lines was conducted. The densification curve was taken from previous experimental data. By using a Origin Graphic tools and Coble sintering model,  the  graph  of densification towards sintering temperature was  used  to  analyze  the stages  of sintering. The microwave and conventional methods are compared. The results show that the alumina ceramics has three stages (initial, intermediate, and final stages) of sintering on both method. The initial stage occurs over a range of temperatures of 800°C and 1000°C, intermediate stage occurs at a temperature range of 1100°C and 1500°C, while a temperature range of 1600°C and 1700°C is the final stages.